1996
DOI: 10.2172/211388
|View full text |Cite
|
Sign up to set email alerts
|

Volatility literature of chlorine, iodine, cesium, strontium, technetium, and rhenium; technetium and rhenium volatility testing

Abstract: This report reviews the voIatili&hterature relevant to iodinerstrontium, cesium and chlorine as might be expected from the vitrification of low-level wastes at Hanford. In addition, the report contains a review of the aqueous chemistry and volatilization behavior of technetium and a proposed surrogate, rhenium. Some preliminary tests of technetium and rhenium volatility have been performed and are reported iii . .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…The use of TiO 2 as an additive in the borosilicate system has been the subject of several investigations. 5,6 Rastogi et al 7 reported that volatility of Cs can be reduced by using a little amount of TiO 2 , possibly due to the formation of thermally stable compounds such as Cs 2 O-4TiO 2 . The effect of TiO 2 on the reduction of Cs volatility was also observed by Kelly 8 during the preparation of glass from zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…The use of TiO 2 as an additive in the borosilicate system has been the subject of several investigations. 5,6 Rastogi et al 7 reported that volatility of Cs can be reduced by using a little amount of TiO 2 , possibly due to the formation of thermally stable compounds such as Cs 2 O-4TiO 2 . The effect of TiO 2 on the reduction of Cs volatility was also observed by Kelly 8 during the preparation of glass from zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…The gaseous byproduct of this reaction is technetium heptoxide, Tc 2 O 7 , which is highly reactive, and able to combine with alkali, to reform alkali pertechnetate, or with hydrogen, to form a pertechnic acid, HTcO 4 [44,45]. The work of Colton, Rard, and Vida have thoroughly studied the thermodynamics of Tc 2 O 7 [46][47][48].…”
Section: O Xtcomentioning
confidence: 99%
“…Although most radionuclides present no challenges to the vitrification of high-level waste, certain radionuclides, especially 137 Cs and 99 Tc, are easily volatilized during vitrification. (Langowski, Darab et al 1996) The behavior of technetium and rhenium in borosilicate glasses has recently been reviewed, (Darab and Smith 1996) and will be discussed only briefly here. A number of Tc(VII) compounds have low boiling points.…”
Section: Behavior Of Technetium In Glassmentioning
confidence: 99%